Recent results in the study of the 20Ne + 130Te collision within the NUMEN project and future perspectives - Soukeras, Vasileios; Cappuzzello, F.; Carbone, D.; Cavallaro, M.; Agodi, C.; Acosta, L.; Boztosun, I.; Brischetto, G. A.; Calvo, D.; Chavez – Lomeli, E. R.; Ciraldo, I.; Delaunay, F.; et al. (HNPS Advances in Nuclear Physics, 2024)
The NUMEN (Nuclear Matrix Elements for Neutrinoless double beta decay) project aims to investigate specific heavy–ion double charge exchange reactions to provide experimentally data driven information about nuclear matrix elements of interest in the context of neutrinoless double beta decay (0νββ). Taking into consideration that 130Te is a candidate nucleus for double beta decay, the 20Ne + 130Te system was experimentally investigated in a multi-channel approach by measuring the complete net of reaction channels, namely elastic and inelastic scattering, double charge exchange, single charge exchange, one– and two–nucleon transfer reactions, characterized by the same initial state interaction. The relevant experimental campaign was carried out at INFN – Laboratori Nazionali del Sud (LNS) in Catania using the Superconducting Cyclotron to accelerate the beams and the MAGNEX magnetic spectrometer to detect the reaction ejectiles. The experimental challenges and the obtained results for the 20Ne + 130Te system are presented and discussed. Since a deeper investigation of the 130Te nucleus as well as all the nuclei which are candidates for 0νββ decay is foreseen within the next phase of NUMEN, the Research and Development activity relevant to the facility upgrade is also discussed.